Internet w placówce opiekuńczo-wychowawczej - Ewelina Milart, Ewelina Milart (Studia Edukacyjne, 2020)
This paper aims to present the specifics of the Blessed M. Karłowska Care and Education Home for Girls in Poznań. At the beginning of my deliberations I referred to the rules prevailing in the institution. I have presented a number of restrictions that result from the internal rules of the center. I described the possibilities of using the Internet which result from prevailing restrictions. I moreover indicated the forms and ways of foster children’s use of the Internet and referred to theoretical reflections on the teenagers’ use of the Internet.